Comparison of esophageal motility impairment caused by Chagas' disease in two age groups - Dantas,Roberto Oliveira (2006)
BACKGROUND: Chagas' disease and the aging process cause loss of neurons of the esophageal myenteric plexus. AIM: To evaluate the esophageal motility impairment caused by Chagas' disease in two age groups. Our hypothesis was that the aging process may cause further esophageal motility impairment in patients with Chagas' disease. METHODS: We studied the esophageal motility of 30 patients with Chagas' disease and dysphagia, with esophageal retention of barium sulfate and an esophageal diameter within the normal range. Fifteen were 34 to 59 years old (younger group, median 51 years) and 15 were 61 to 77 years old (older group, median 66 years). As a control group we studied 15 subjects aged 33 to 58 years (median 42 years) and 7 subjects aged 61 to 73 years (median 66 years). The esophageal contractions were measured by the manometric method with continuous perfusion after five swallows of a 5 mL bolus of water at 2, 7, 12 and 17 cm below the upper esophageal sphincter. RESULTS: Patients with Chagas' disease had lower amplitude of contractions and fewer peristaltic, more simultaneous, and more non-conducted contractions than controls. Older patients with Chagas' disease had lower amplitude of contractions in the distal esophagus (mean ± SE: 30.8 ± 4.3 mm Hg) than younger patients (51.9 ± 8.6 mm Hg). From 12 to 17 cm, older patients had more non-conducted (41%) and fewer peristaltic (8%) contractions than younger patients (non-conducted: 16%, peristaltic: 21%). CONCLUSION: Older patients with Chagas' disease with clinical and radiological examinations similar to those of younger patients had motility alterations suggesting that the aging process may cause further deterioration of esophageal motility.